The Quality Characteristics of Ready-to-Eat Empal Gentong Affected by Meat Pre-Cooking - Triyannanto, Endy; Febrisiantosa, Andi; Kusumaningrum, Annisa; Amri, Aldicky Faizal; Fauziah, Safna; Sulistyono, Eki Prilla; Dewandaru, Bayu Murti; Nurhikmat, Asep; Susanto, Agus (2022)
The purpose of this research was to examine the effectiveness of pre-cooking treatments on the quality characteristics of ready-to-eat (RTE) empal gentong. Raw beef meat was pre-cooked in water bath at 90° for 0 min (C), 10 min (T1), 20 min (T2), and 30 min (T3) prior to retorting process at 121° and pressure at 70,000 Pa. Results showed that pre-cooking treatments in all treated samples could reduce fat contents in empal gentong's meat by 0.02 (T1), 0.28 (T2), and 1.13 (T3) respectively. Highest precooking time tends to increase the pH and CIE a∗ values. However, CIE b∗ values, water holding capacity, and sensory analysis were not affected by pre-cooking duration which must have been affected by sterilization process after pre-cooking. In conclusion, pre-cooking treatment before sterilization in producing empal gentong is a probable technique to reduce its fat content and improve its physical quality. A specific treatment at 90°C for 10 min is recommended to achieve optimum quality of RTE empal gentong's meat. © Korean Society for Food Science of Animal Resources.